Ryanodine-induced vasoconstriction of the gerbil spiral modiolar artery depends on the Ca2+ sensitivity but not on Ca2+ sparks or BK channels. Issue 1 (December 2016) - Krishnamoorthy, Gayathri; Reimann, Katrin; Wangemann, Philine
Abstract Background In many vascular smooth muscle cells (SMCs), ryanodine receptor-mediated Ca2+ sparks activate large-conductance Ca2+ -activated K+ (BK) channels leading to lowered SMC [Ca2+ ]i and vasodilation. Here we investigated whether Ca2+ sparks regulate SMC global [Ca2+ ]i and diameter in the spiral modiolar artery (SMA) by activating BK channels. Methods SMAs were isolated from adult female gerbils, loaded with the Ca2+ -sensitive flourescent dye fluo-4 and pressurized using a concentric double-pipette system. Ca2+ signals and vascular diameter changes were recorded using a laser-scanning confocal imaging system. Effects of various pharmacological agents on Ca2+ signals and vascular diameter were analyzed. Results Ca2+ sparks and waves were observed in pressurized SMAs. Inhibition of Ca2+ sparks with ryanodine increased global Ca2+ and constricted SMA at 40 cmH2 O but inhibition of Ca2+ sparks with tetracaine or inhibition of BK channels with iberiotoxin at 40 cmH2 O did not produce a similar effect. The ryanodine-induced vasoconstriction observed at 40 cmH2 O was abolished at 60 cmH2 O, consistent with a greater Ca2+ -sensitivity of constriction at 40 cmH2 O than at 60 cmH2 O. When the Ca2+ -sensitivity of the SMA was increased by prior application of 1 nM endothelin-1, ryanodine induced a robust vasoconstriction at 60 cmH2 O. Conclusions The results suggest that Ca2+ sparks, while present, do not regulate vascular diameter in the SMA by activating BK channels and that the regulation of vascular diameter in the SMA is determined by the Ca2+ -sensitivity of constriction.